2022
DOI: 10.1001/jamahealthforum.2022.2826
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicare Advantage Premiums With Measures of Quality and Patient Experience

Abstract: ImportanceQuality of care varies substantially across Medicare Advantage plans. The price information that Medicare Advantage enrollees are most likely to consider when selecting a Medicare Advantage plan is the monthly premium. Enrollees may select plans to minimize premium or, alternatively, use premium as a proxy for quality and select plans with higher premiums; however, quality implications of these choices are unknown.ObjectiveTo determine the extent to which the quality of care offered by Medicare Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Similar to prior research using CAHPS data to evaluate patient experience, we applied the heuristic of 0.1 point to indicate a small, 0.3 points a medium, and 0.5 points a large difference in quality. 21,28 We found that the differences attributable to plans adopting both benefits were small to medium.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Similar to prior research using CAHPS data to evaluate patient experience, we applied the heuristic of 0.1 point to indicate a small, 0.3 points a medium, and 0.5 points a large difference in quality. 21,28 We found that the differences attributable to plans adopting both benefits were small to medium.…”
Section: Discussionmentioning
confidence: 81%
“…However, we found no statistically significant association between plans adopting only a PHRB or SSBCI and a change in mean enrollee plan ratings. Similar to prior research using CAHPS data to evaluate patient experience, we applied the heuristic of 0.1 point to indicate a small, 0.3 points a medium, and 0.5 points a large difference in quality . We found that the differences attributable to plans adopting both benefits were small to medium.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As the findings of Haviland and colleagues suggest, 1 the Medicare Advantage program could be improved by helping beneficiaries to choose better plans for themselves. Broader strategic reforms will likely be needed as well.…”
Section: Jama Healthmentioning
confidence: 99%
“…For this reason, many scholars studying the US system examine aspects of how well the market system works. One strand of this research explores the associations between price and quality, and the study by Haviland and colleagues in this issue of JAMA Health Forum exemplifies this research . Specifically, the authors analyze the associations between premiums and quality in the Medicare Advantage market, which is composed of private health plans that served almost half of eligible Medicare beneficiaries in 2021.…”
mentioning
confidence: 99%